Legalism anthropology and history - Dresch, Paul.; Skoda, Hannah, 1981- (Oxford : Oxford University Press, 2012)
Leading historians and anthropologists with an interest in law gather to analyse the nature and meaning of law in diverse societies.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Law and anthropology; Law -- Philosophy